Avaliação da massa muscular medida pela tomografia computadorizada abdominal como preditor de morbidade e mortalidade em pacientes na fase não dialítica da doença renal crônica - Bichels, Andre Valente [UNIFESP] (2019)
Background: In chronic kidney disease (CKD), multiple metabolic and nutritional abnormalities contribute to the loss of skeletal muscle mass. Muscle mass is a key element for evaluation of nutritional disturbances, and low muscle mass is associated with increased morbidity and mortality. An accurate method for muscle mass evaluation that is not subject to errors caused by perturbations in the uremic milieu remains a challenge for the nephrology community. Methods: This is a prospective observational cohort study. We evaluated 223 non-dialyzed CKD patients [60.3±10.6 years; 64% men; 50% diabetics; glomerular filtration rate (GFR) 27.3±16.3 ml/min/1.73m2]. Muscle mass was measured by computed tomography at the third lumbar vertebra region (CTMM-L3) using the Slice-O-Matic software and analyzed according to percentile adjusted by gender. Nutritional parameters, laboratory data and comorbidities were evaluated, and mortality was followed-up for 4 years. Results: During the study period 63 patients died, and the main cause of death was cardiovascular disease. Patients who died were older, had lower GFR, hemoglobin and albumin, as well as lower muscle markers. CTMM-L3 below the 25th percentile was associated with higher mortality according to the Kaplan-Meier curve (P=0.017), and in Cox-regression analysis [crude hazard ratio, HR, 1.87 (95% confidence interval, CI, 1.11-3.16)], also when adjusting for potential confounders [HR 1.83 (CI 1.02-3.30)]. Conclusions: Low muscle mass measured by computed tomography at the third lumbar vertebra region is an independent predictor of increased mortality in non-dialyzed CKD patients.